Person-centred care transitions for people with stroke: study protocol for a feasibility evaluation of codesigned care transition support - Maria Flink; Jan Hasselström; Malin Tistad; Charlotte Ytterberg; Lena von Koch; Marie Elf; Sebastian Lindblom; Ann Charlotte Laska; Bo Christer Bertilsson; Carmen Wärlinge (BMJ Open)
Background Care transitions following stroke should be bridged with collaboration between hospital staff and home rehabilitation teams since well-coordinated transitions can reduce death and disability following a stroke. However, health services are delivered within organisational structures, rather than being based on patients’ needs. The aim of this study protocol is to assess the feasibility, operationalised here as fidelity and acceptability, of a codesigned care transition support for people with stroke.Methods This study protocol describes the evaluation of a feasibility study using a non-randomised controlled design. The codesigned care transition support includes patient information using videos, leaflets and teach back; what-matters-to me dialogue; a coordinated rehabilitation plan; bridged e-meeting; and a message system for cross-organisational collaboration. Patients with stroke, first time or recurrent, who are to be discharged home from hospital and referred to a rehabilitation team in primary healthcare for continued rehabilitation in the home will be included. One week after stroke, data will be collected on the primary outcome, namely satisfaction with the care transition support, and on the secondary outcome, namely health literacy and medication adherence. Data on use of healthcare will be obtained from a register of healthcare contacts. The outcomes of patients and significant others will be compared with matched controls from other geriatric stroke and acute stroke units, and with matched historic controls from a previous dataset at the intervention and control units. Data on acceptability and fidelity will be assessed through interviews and observations at the intervention units.Ethics and dissemination Ethical approvals have been obtained from the Swedish Ethical Review Authority. The results will be published open-access in peer-reviewed journals. Dissemination also includes presentation at national and international conferences.Discussion The care transition support addresses a poorly functioning part of care trajectories in current healthcare. The development of this codesigned care transition support has involved people with stroke, significant other, and healthcare professionals. Such involvement has the potential to better identify and reconceptualise problems, and incorporate user experiences.Trial registration number http://www.clinicaltrials.gov id: NCT02925871. Date of registration 6 October 2016.Protocol version 1.